Environmental UV Radiation: Impact on Ecosystems and Human Health and Predictive Models Proceedings of the NATO Advanced Study Institute on Environmental UV Radiation: Impact on Ecosystems and Human Health and Predictive Models Pisa, Italy June 2001 - Ghetti, Francesco; Checcucci, Giovanni; Bornman, Janet F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This publication originates from the NATO Advanced Study Institute on Environmental Radiation: Impact on Ecosystems and Human Health and Predictive Models, held in Pisa, Italy, in June 2001. The book offers not only basic information on the action mechanisms of UV radiation on ecosystems and various biological systems, but also a picture of the possible scenarios of the long-term global increase of environmental UV radiation, with emphasis on the research aspects aimed at the proper quantitative assessment of risk factors and the formulation of reliable predictive models. The purpose of the authors is to present a critical discussion on how changes in UV radiation will affect ecosystems and the biological processes needed to sustain life on Earth and to provide useful hints for future actions of governmental and international agencies, as well as non-governmental organizations. The book is structured in four sections: the first one is devoted to a general overview of the consequences of ozone depletion and to the basic concepts of radiation measurements and monitoring; the other three sections are devoted to the effects on plants, aquatic ecosystems and human health.
Historical Overview of Ozone Trends and Future Scenarios -- Basic Concepts of Radiation -- Solar Radiation and Its Measurement -- Medical and Environmental Effects of UV Radiation -- Quantification of Biological Effectiveness of UV Radiation -- Use and Evaluation of Biological Spectral UV Weighting Functions for the Ozone Reduction Issue -- Response to UV-B Radiation: Weighting Functions and Action Spectra -- Eldonet - European Light Dosimeter Network -- Genetic and Molecular Analysis of DNA Damage Repair and Tolerance Pathways -- UV-B and UV-A Radiation Effects on Photosynthesis at the Molecular Level -- Potential Effects of UV-B on Photosynthesis and Photosynthetic Productivity of Higher Plants -- Detecting Stress-Induced Reactive Oxygen Species in Plants Under UV Stress -- Non-Damaging and Positive Effects of UV Radiation on Higher Plants -- Impact of UV Radiation on the Aquatic Environment -- Underwater Radiation Measurements: Consequences of an Increased UV-B Radiation -- Influence of Ultraviolet Radiation on the Chromophoric Dissolved Organic Matter in Natural Waters -- Impact of UV Radiation on Rice-Field Cyanobacteria: Role of Photoprotective Compounds -- Effect of UV-B Radiation on Ciliated Protozoa -- UV Radiation, DNA Damage, Mutations and Skin Cancer -- Ultraviolet Radiation and the Eye -- Student Abstracts.
Keywords: ENVIRONMENTAL SCIENCES; PLANT ECOLOGY; CLIMATIC CHANGES; ENVIRONMENTAL PROTECTION; ENVIRONMENTAL MEDICINE; ENVIRONMENTAL TOXICOLOGY; ENVIRONMENT; EFFECTS OF RADIATION/RADIATION PROTECTION; CLIMATE CHANGE; PLANT ECOLOGY; ENVIRONMENTAL HEALTH; ECOTOXICOLOGY